Examining the First Peer-to-Peer Mentorship Program (F1Doctors) for International Medical Students - Jaber Chehayeb, Rachel; SenthilKumar, Gopika; Saade, Ziad; Gallo Marin, Benjamin; Aghagoli, Ghazal; Virji, Azan Zahir (Journal of Interdisciplinary Studies in Education, 2022)
In this study, we report international medical students in the United States and conduct an analysis of the first, peer-to-peer, national mentorship program for international medical students and international pre-med applicants in the US (F1Doctors). We used analyzed survey data collected through F1Doctors and the Association of American Medical Colleges yearly matriculation reports. Results indicated that the average college grade point average (GPA) and Medical College Admission Test score (MCAT) of international applicants was higher than that of all applicants. Additionally, non-US applicants reported facing numerous unique challenges such as limited access to extracurricular opportunities and difficulty finding mentors who are familiar with the application process. International applicants have the potential to increase the diversity of healthcare professionals, and F1Doctors is the first platform to support international healthcare applicants in the US.